The Inner Areas Italian question - Cristina Casadei (Anuari d’Arquitectura i Societat)
Within the theme of depopulation and overcrowding, the article proposes a reflection on the so-called ‘Inner Areas’ Italian question and their re-actualization. The issue concerns the territories now marginalized due to a continuous process of depopulation that began after World War II and has become more acute in recent years. The issue attracts attention since inland areas constitute about 61% of the national territory and coincide with the rugged and mountainous, Apennine and Alpine, and sometimes hilly regions of the peninsula, mainly characterized by rural areas. These territories suffer from reduced employment and land use, inadequate services, and communication infrastructure. But, precisely this critical condition has made today these areas preserve remarkable environmental and historical-cultural qualities, absent or lacking in urban centres, understood as values to be recovered, at the base of a possible development strategy. The discussion starts from the assumption that there is a close relationship between roads and land occupation and considers the territory of Inner Southern Etruria, which falls within the perimeter of the Inner Areas. Then it proposes a strategy for reactivating the landscape that starts by recovering the capillary and minute road network that permeates it. This dense network of travels, in this case, referred to the ancient via Clodia, can be traced and interpreted today as a structure for crossing and actualizing marginalized regions.